2014
DOI: 10.12688/f1000research.4396.1
|View full text |Cite
|
Sign up to set email alerts
|

CETP inhibitors and cardiovascular disease: Time to think again

Abstract: Inhibition of cholesteryl ester transfer protein (CETP) lowers plasma low-density lipoprotein cholesterol concentration and raises high-density lipoprotein (HDL) cholesterol, suggesting it might prevent cardiovascular disease (CVD). From the outset, however, the concept has been controversial owing to uncertainty about its effects on HDL function and reverse cholesterol transport (RCT). Although there has long been good evidence that CETP inhibition reduces atherosclerosis in rabbits, the first information on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…The first observational prospective cohort study that has proven the role of CETP as a risk factor for cardiovascular diseases (CVDs) was in 2006. After that, CETP inhibitors have been evaluated in several randomized controlled trials . Elevated CETP levels were found to associate with dyslipidemia of metabolic diseases, insulin resistance, hypertriglyceridemia, and ultimately with premature atherosclerosis .…”
Section: Development Of Newer Hypolipidemic Molecules That Act Througmentioning
confidence: 99%
See 1 more Smart Citation
“…The first observational prospective cohort study that has proven the role of CETP as a risk factor for cardiovascular diseases (CVDs) was in 2006. After that, CETP inhibitors have been evaluated in several randomized controlled trials . Elevated CETP levels were found to associate with dyslipidemia of metabolic diseases, insulin resistance, hypertriglyceridemia, and ultimately with premature atherosclerosis .…”
Section: Development Of Newer Hypolipidemic Molecules That Act Througmentioning
confidence: 99%
“…After that, CETP inhibitors have been evaluated in several randomized controlled trials. 32 Elevated CETP levels were found to associate with dyslipidemia of metabolic diseases, insulin resistance, hypertriglyceridemia, and ultimately with premature atherosclerosis. 33 The concept of CETP inhibition came into the field of atherosclerosis because of its immense potential to increase HDL level and also its anti-atherosclerotic activities.…”
Section: Development Of Newer Hypolipidemic Molecules That Act Thromentioning
confidence: 99%
“…Although the elevation of plasma high‐density lipoprotein (HDL) protects against atherosclerosis by mechanisms involving cellular removal of cholesterol, inhibition of oxidation, apoptosis, inflammation and restoration of endothelial function, raising HDL by inhibiting CETP has not been effective in the prevention of coronary vascular disease (CVD) . Nonetheless, although the elevation of HDL by inhibitors of CETP and niacin has increased activity on cellular cholesterol efflux and anti‐inflammatory properties , besides reducing concentrations of pro‐atherogenic lipoproteins (apoB‐LP), these pharmacological interventions have failed in preventing human atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…Higher frequency rate of cardiovascular disease was related to both high and low CETP concentration or CETP mRNA . However, in a 2014 review, Miller listed six population investigations where the concentration of CETP in plasma was reciprocally related to cardiovascular disease (CVD). On the other hand, a meta‐analysis by Thomson in 2008 , including 46 studies, concluded that CETP genotypes that are associated with moderate inhibition of the CETP activity showed weakly inverse correlation with coronary artery disease risk.…”
Section: Introductionmentioning
confidence: 99%
“…After reviewing the literature up to May 2014, Miller ( 2014 ) concluded that CETP inhibition is more likely to increase CVD than prevent it, and was of the opinion that ongoing trials should be stopped. Since then several further pertinent studies have been published.…”
mentioning
confidence: 99%